Effect of Penetration Enhancers on Drug Nail Permeability from Cyclodextrin/Poloxamer-Soluble Polypseudorotaxane-Based Nail Lacquers - Elena Cutrín-Gómez; Soledad Anguiano-Igea; M. Begoña Delgado-Charro; José Luis Gómez-Amoza; Francisco J. Otero-Espinar (MDPI AG, 2018)
Nail delivery has interest for local treatment of nail diseases. Nevertheless, the low permeability of drugs in the nail plaque precludes the efficacy of local treatments. The use of penetration enhancers can increase drug permeability and improve the efficacy of the treatment of nail pathologies. In this work, different chemical substances have been evaluated as potential penetration enhancers. With this aim, the effect of different substances such as sodium lauryl sulfate (SLS), polyethylene glycol 300 (PEG 300), carbocysteine, N-acetylcysteine, lactic acid, potassium phosphate, Labrasol® and Labrafil® in the microstructure, nail surface and drug permeability has been evaluated. The models obtained by mercury intrusion porosimetry and PoreXpert™ software show a more porous structure in nails treated with different enhancers. Permeation studies with bovine hooves and nails revealed that all the hydroalcoholic lacquers developed, and particularly those prepared with SLS, provide better nail penetration of the drugs ciclopirox olamine and clobetasol propionate. Results have shown that the increase of the drug penetration in the nail is caused by the formation of a porous random microstructure and by the decrease of the contact angle between lacquers and the surface or the nail plaque. The presence of SLS produces an improvement in the spreading of the solution on the nail surface and promotes the penetration of the solution into the nail pores. The hydroalcoholic lacquer, elaborated with cyclodextrin/poloxamer soluble polypseudorotaxane and sodium lauryl sulfate as an enhancer, allowed the rate of diffusion and penetration of the active ingredient within the nail to be significantly higher than obtained with the reference lacquers when using either ciclopirox olamine or clobetasol propionate as the active ingredient.